2019
DOI: 10.1021/acs.energyfuels.9b00657
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Drying Behaviors of Brown Coal and Its Pore Structures

Abstract: Drying behaviors of brown coal are affected by internal water diffusion, which is controlled by pore structures. To diminish the effect of functional groups on drying, drying behaviors and pore structures of only one kind of coal dried at different heating rates and atmospheres were investigated. The final drying temperature was kept constant. The relationships between pore structures, including specific surface area (S BET), volume of mesopores (V meso), volume of macropores (V macro), volume of total pores (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Therefore, the pore structure distribution of coal gradually transitions from mesopores to micropores as the water evaporation time increases. Micropores are not conducive to methane diffusion in coal. , Thus, after treatment with the HWPI, the pore structure of coal changes, and the dense pore structure significantly reduces the risk of spontaneous coal combustion. However, the amount of water in the HWPI decreases as the drying time increases, weakening or annulling the function of the original liquid membrane isolation, gradually exposing the surface of the pore structures, and increasing the risk of spontaneous combustion .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the pore structure distribution of coal gradually transitions from mesopores to micropores as the water evaporation time increases. Micropores are not conducive to methane diffusion in coal. , Thus, after treatment with the HWPI, the pore structure of coal changes, and the dense pore structure significantly reduces the risk of spontaneous coal combustion. However, the amount of water in the HWPI decreases as the drying time increases, weakening or annulling the function of the original liquid membrane isolation, gradually exposing the surface of the pore structures, and increasing the risk of spontaneous combustion .…”
Section: Resultsmentioning
confidence: 99%
“…An adsorption isotherm is sufficient to calculate the fractal dimension. The models of Brunauer–Emmett–Teller (BET), Langmuir, and Frenkel–Halsey–Hill (FHH) can be used to calculate fractal dimension values based on the gas adsorption isotherm. In these models, the FHH model is very concise and has been proved to be the most efficient.…”
Section: Introductionmentioning
confidence: 99%
“…He et al [ 26 ] investigated the relationship between water release behaviour and pore evolution during lignite thermal drying and concluded that most of the water exists in pores of 26–100 nm in size, and that the macroporous structure is more likely to be damaged than other pore structures. Feng et al [ 27 ] studied the drying behaviour and pore structure of lignite under different heating rates and drying atmospheres and discussed the relationship between the specific surface area, volume of mesopores and macropores, total pore volume, fractal dimension, and drying characteristics. Wang et al [ 28 ] observed the pore structure of Xilingol lignite during microwave drying and found that the failure mechanism of the pore structure mainly includes (a) destruction of the pore structure caused by shrinkage force during moisture removal, (b) opening and crosslinking of blind and closed pores, and (c) thermal decomposition of coal organic macromolecules into small molecular structures at high temperatures.…”
Section: Introductionmentioning
confidence: 99%